2020
DOI: 10.9734/ejmp/2020/v31i330219
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antimicrobial Studies of Some Hemi-parasitic West African Plants

Abstract: The study investigated the antioxidant and antimicrobial activities of some West African hemi-parasitic plants, which comprised Tapinanthus bangwensis (TB), Tapinanthus globiferus (TG) and Globimetula braunii (GB), used in Nigerian ethnomedicine for the management of skin and other microbial infections. This was with a view to determining the most active plant extract and fraction. The leaf and stem of each plant was separately air-dried, powdered and macerated in ethanol-H20 (8:2). The extracts were subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Antimicrobial and antioxidant properties of different solvent extract and fractions of G. braunii have been reported. 35,36 Apart from the antimicrobial properties of medicinal plants, their antioxidant potential is a significant feature that can be screened for antiplasmodial potential. 37,38 This antioxidant potential may be an indicator of the therapeutic mechanism of antimalarial herbs.…”
Section: B a Cmentioning
confidence: 99%
“…Antimicrobial and antioxidant properties of different solvent extract and fractions of G. braunii have been reported. 35,36 Apart from the antimicrobial properties of medicinal plants, their antioxidant potential is a significant feature that can be screened for antiplasmodial potential. 37,38 This antioxidant potential may be an indicator of the therapeutic mechanism of antimalarial herbs.…”
Section: B a Cmentioning
confidence: 99%
“…Three ursane-type triterpenes (1-3), three phenolics (4-6) and two phenolic derivatives (7 and 8) were isolated and identified in our study of G. braunii living on Leucena leucocephala (Fabaceae), its host, which marked the first report of these compounds in the plant and the family Loranthaceae. Previous phytochemical studies on the plant have shown the presence of tannins, phenolics, flavonoids, terpenoids and sterols [8,10], while compounds reportedly isolated include lupeol-type triterpenes (globrauneine A-F, lupeol and lupeol acetate), lactones and flavonoids (quercetin, quercitrin, rutin and avicularin), identified in the G. braunii living on Piliostigma thonningi (Fabaceae). Perhaps, this new additions to the repository of compounds in G. braunii might have occurred because of plant-host specificity, which was reported to play a critical role in the quality and quantity of constituents elicited by Mistletoes as well as its influence on their biological properties [4].…”
Section: Structure Elucidationmentioning
confidence: 99%
“…They were powdered (5.0 kg) and macerated with 25 L of EtOH-H 2 O (4:1) at room temperature for 72 h with frequent agitation. This extraction method was a follow-up process to the previous study on the plant [8]. The filtrate was concentrated to dryness in vacuo on a Heidolph RE 400 Rotary Evaporator set at 45 • C and 100 rpm.…”
Section: Plant Extraction and Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…bojeri on Reunion was attributed to the loss of its hypothetically main dispersers (flying foxes, doves, and parrots) since human colonization of the island (Albert et al, 2017). Many species of African mistletoes are being studied by ethnobotanists due to their traditional use in spiritual practices as well as increasing exploitation in officinal medicine and by herbalists as “all‐healing,” “bone‐setting,” and “fertility‐boosting” drugs (Koffi et al, 2020; Oriola et al, 2020). At the same time, due to their broad host range and tendency to spread rapidly, many mistletoe species have gained a reputation as notorious pests that cause significant losses in tree crops (Dibong et al, 2008).…”
Section: Introductionmentioning
confidence: 99%